Characterization of Oxacillin-Resistant and Oxacillin-Susceptible mecA-Positive Staphylococcus pseudintermedius from Skin Lesions and Nasal Cavities of Dogs with Clinical Pyoderma - Putu Ayu Sisyawati Putriningsih; Jaruwan Kampa; Suphattra Jittimanee; Patchara Phuektes (Animals, 2024)
Understanding the epidemiology of mecA-positive Staphylococcus pseudintermedius strains, including those that are oxacillin-susceptible but potentially inducible to resistance, is crucial for developing effective treatment strategies and mitigating public health risks. This study characterized 87 mecA-positive S. pseudintermedius isolates obtained from skin lesions and nasal orifices of 46 dogs with pyoderma enrolled at a referral hospital in Thailand between 2019 and 2020. All isolates underwent antibiogram profiling, SCCmec typing, and pulsed-field gel electrophoresis (PFGE) for phenotypic and genetic analysis. Among the 87 isolates, 33 isolates (37.9%) recovered from 15 dogs were oxacillin-resistant (OR-MRSP), while 54 isolates (62.1%) from 31 dogs were oxacillin-susceptible (OS-MRSP). All OR-MRSP isolates exhibited multidrug resistance (MDR), and 44% of the OS-MRSP isolates also showed MDR. SCCmec typing revealed type V as predominant among OR-MRSP isolates (69.7%), while many oxacillin-susceptible isolates (70.4%) were non-typeable. The OR-MRSP isolates from the same dog showed consistent antibiogram and SCCmec types, while OS-MRSP isolates displayed both identical and diverse patterns. No dominant pulsotypes were observed among the OR-MRSP or OS-MRSP strains. Genetic diversity was also noted among the isolates within the same dogs and among the others, highlighting the complexity of S. pseudintermedius colonization and infection dynamics in pyoderma-affected dogs.